Comparative evaluation of epidural bupivacaine alone and bupivacaine combined with magnesium sulfate in providing postoperative analgesia: a meta-analysis of randomized controlled trials - Li, Li-Qin (BMC Anesthesiol, 2020)
BACKGROUND: The comparative efficacy of epidural bupivacaine alone and bupivacaine combined with magnesium sulfate in providing postoperative analgesia remains controversial. METHODS: We searched Mediline (OvidSP), EMBASE (OvidSP) and Cochrane Central Register of Controlled Trials (CENTRAL) to identify trials that compared epidural bupivacaine and magnesium sulfate combination (intervention) with bupivacaine alone (control). Grading of Recommendations, Assessment, Development and Evaluations (GRADE) framework was used to assess the quality of evidence. RESULTS: Eleven studies fulfilled our inclusion criteria after screening. We found that epidural bupivacaine combined with magnesium sulfate could prolong the time for first rescue analgesics (SMD 4.96; 95% CI [2.75, 7.17], P < 0.00001, I(2) = 98%), reduce the number of patients who need rescue analgesics (RR 0.38; 95% CI [0.20, 0.74], P = 0.004, I(2) = 75%) and requirement for rescue analgesics (SMD -2.65; 95% CI [− 4.23, − 1.06], P = 0.001, I(2) = 96%). CONCLUSIONS: Magnesium suifate as an adjuvant of epidural bupivacaine improved postoperative analgesia. However, we rated the quality of evidence to be very low because of high heterogeneity, imprecise of results and small sample sizes. Furthermore, further large high-quality trials are still needed to confirm the effects of magnesium sulfate on postoperative analgesia.